The unemployed piqueteros of Argentina : active rejection of an exclusionary form of democracy - Colmegna, Paula (Universidad Nacional de Quilmes, 2003)
This paper will focus on the Argentinean Piquetero movements of the unemployed and will address, by looking at their struggle, the transformations that have been set in motion in the Argentinean society as a result of the implementation of a neoliberal model with its consequent structural adjustment policies. I will focus on the trajectory of the Piqueteros, how they came into existence and later became the symbol of the struggle of many unemployed Argentineans against both political institutions and neoliberal policies. I will try to understand their objectives; internal heterogeneity, changing identities and forms of resistance, as well as the relationship that they establish with other socio-political actors and the various discourses that are created around them. I will further discuss how the Piqueteros struggle has been transformed in the light of the current socio-economic and political crisis and will also try to illustrate the role that the Piqueteros had in symbolising the present struggles against the model.